ESTRO ACROP guidelines for the delineation of lymph nodal areas in upper gastrointestinal malignancies. (November 2021) - Valentini, Vincenzo; Cellini, Francesco; Riddell, Angela; Brunner, Thomas B.; Roeder, Falk; Giuliante, Felice; Alfieri, Sergio; Manfredi, Riccardo; Ardito, Francesco; Fiorillo, Claudio; Porziella, Venanzio; Morganti, Alessio G.; et al.
Highlights: Target delineation is crucial, but hampered by variability. Variability in delineations will lead to differences in irradiated volumes and clinical outcome. A key issue remains the delineation of clinically negative or elective lymph-nodal stations. Guidelines (GL) available in literature are not consistent in their recommendations on anatomical boundaries. This GL deals delineation of lymph-nodal involved in UGI for preoperative (or definitive) setting Abstract: The European SocieTy for Radiation and Oncology -Advisory Committee on Radiation Oncology Practice (ESTRO-ACROP) endorsed a project to provide guidelines (GL) for the identification and delineation of clinically negative lymph-nodal stations (LNs) involved in upper gastrointestinal clinical scenarios. The presented GL is focused on preoperative (or definitive) setting. The project aim is to improve the consistency of clinical target volume (CTV) delineation by providing: a description of the anatomical boundaries of the LNs; a radiological computed tomography-based atlas depicting the LNs areas; a free, web-based, interactive example case for independent training of radiation oncologists on LNs delineation according to the presented GL, by both qualitative and quantitative analysis (through the FALCON EduCase platform). This project was carried out with the intention to facilitate and improve uniformity of future upper gastrointestinal guidelines on nodal CTV delineation. We report methodology and results from the collaboration of a working group panel selected by the ESTRO-ACROP.